Characterisation of Zeolite, Polyaniline and Zeolite/Polyaniline As antifouling Materials for Marine Applications - Ahdash, Abdelsalam (2013)
In this paper, the basic synthesis of encapsulated zeolite, polyaniline and zeolite/polyaniline composite as self-healing core materials for antifouling coatings was studied through interfacial polymerization. All materials were synthesized by using ammonium persulphate as an oxidant agent. Field Emission Scanning electron microscope (FESEM), X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Differential Scanning Calorimetry (DSC) techniques were used to characterize the synthesized materials. This paper aims to study on synthesis and characterization of zeolite, polyaniline and zeolite/polyaniline composite as self-healing core materials for antifouling applications. FESEM revealed that a smooth and homogeneous microstructure of materials. XRD results showed the high crystalline nature of all materials. FTIR showed the successful synthesis of the three materials. Finally, DSC results revealed appreciable Thermal properties of the developed materials.